2004
DOI: 10.1123/ijsnem.14.4.443
|View full text |Cite|
|
Sign up to set email alerts
|

The Effects of Creatine Supplementation on Cardiovascular, Metabolic, and Thermoregulatory Responses during Exercise in the Heat in Endurance-Trained Humans

Abstract: The effects of creatine (Cr) supplementation on cardiovascular, metabolic, and thermoregulatory responses, and on the capacity of trained humans to perform prolonged exercise in the heat was examined. Endurance-trained males (n = 21) performed 2 constant-load exercise tests to exhaustion at 63 +/- 5 % VO(2max) in the heat (ambient temperature: 30.3 +/- 0.5 C) before and after 7 d of Cr (20 g x d (-1 ) Cr + 140 g x d (-1 ) glucose polymer) or placebo. Cr increased intracellular water and reduced thermoregulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 38 publications
6
64
0
1
Order By: Relevance
“…Polyviou et al (2012) extended this research and reported that Cr combined with Gly and α-lipoic acid (Ala) had similar effects as the Cr/Gly/glucose combination used by Easton et al (2007) when performing constant load exercise in the heat followed by a 10-mile time trial in a hot humid environment. Despite the fairly consistent effects of Cr-induced hyperhydration (with and without enhancement by other hyperhydrating compounds) on thermoregulatory and cardiovascular responses in the previous studies described, exercise performance in the heat was not enhanced (Kilduff et al 2004;Easton et al 2007;Beis et al 2011;Polyviou et al 2012). It is possible that the exercise trials were not of sufficient duration and intensity for Cr-induced hyperhydration to have a significant effect on performance.…”
Section: Cr Supplementation and Endurance (Aerobic) Exercise Performancementioning
confidence: 67%
See 2 more Smart Citations
“…Polyviou et al (2012) extended this research and reported that Cr combined with Gly and α-lipoic acid (Ala) had similar effects as the Cr/Gly/glucose combination used by Easton et al (2007) when performing constant load exercise in the heat followed by a 10-mile time trial in a hot humid environment. Despite the fairly consistent effects of Cr-induced hyperhydration (with and without enhancement by other hyperhydrating compounds) on thermoregulatory and cardiovascular responses in the previous studies described, exercise performance in the heat was not enhanced (Kilduff et al 2004;Easton et al 2007;Beis et al 2011;Polyviou et al 2012). It is possible that the exercise trials were not of sufficient duration and intensity for Cr-induced hyperhydration to have a significant effect on performance.…”
Section: Cr Supplementation and Endurance (Aerobic) Exercise Performancementioning
confidence: 67%
“…As oral Cr supplementation has consistently been shown to increase TBW and ICW (Francaux and Poortmans 1999;Saab et al 2002), several studies have hypothesised Cr may confer thermogenic effects through augmented hydration. Kilduff et al (2004) investigated whether these hydrating effects of Cr loading could be harnessed to influence cardiovascular, metabolic and thermoregulatory responses during exercise in the heat. To test this hypothesis, 21 endurance-trained males performed 2 constant-load exercise tests to exhaustion at 63 ± 5 % of maximal oxygen uptake ( O 2max ) in a climatic chamber set at 30.3 ± 0.5 ºC before and after 7 days of either Cr or placebo.…”
Section: Cr Supplementation and Endurance (Aerobic) Exercise Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Os dados encontrados estão de acordo com outros estudos 1,4,[11][12][13][16][17][18][19] , nos quais utilizaram protocolo semelhante, usando 20 a 25g/dia de creatina durante 5 a 7 dias, e demonstraram aumento de peso já no término da fase de carregamento de creatina. No estudo de Powers et al 1 , homens e mulheres treinados receberam 25g/dia por sete dias em fase de carregamento com creatina monohidratada, em que os participantes tiveram aumento no peso (75,54 ± 17,67kg e 76,29 ± 18,04kg), água corporal total (41,98 ± 11,78L e 43,35 ± 12,19L) e após a fase de manutenção (5g/dia por 21 dias), mantiveram de forma semelhante os parâmetros aumentados de peso (76,86±18,07kg), água total (44,02±12,37L) quando comparado ao momento pré-suplementação.…”
Section: Discussionunclassified
“…It has been Buford et al [31] proposed that there is no difference between following a CR supplementation programme to increase PCr stores, and completing a carbohydrate loading programme to enhance glycogen stores [31]. It is worth noting that many researchers have argued that banning CR would in fact be unethical as it has been linked to reductions in musculoskeletal injuries [57], heat stress [58], and decreases in rehabilitation periods [59], as well as being a naturally occurring compound.…”
Section: Renal Problems Recordedmentioning
confidence: 99%